Postoperative delirium in children in undergoing treatment of congenital septal heart defects - A. A. Ivkin; E V. Grigoriev; A. V. Tsepokina; D. L. Shukevich (Вестник анестезиологии и реаниматологии)
The objective: to establish the prevalence of postoperative delirium (POD) and the influence of various factors in intra- and postoperative periods on its occurrence in children with septal congenital defects requiring surgical interventions with cardiopulmonary bypass (CPB).Subjects and methods: 40 children from 6 to 36 months and weighing from 7.5 to 15 kg were enrolled in the study; they underwent planned radical surgery of septal CHD with cardiopulmonary bypass. In the postoperative period, all patients were tested using the Cornell Assessment for Pediatric Delirium validated for children of this age. Cerebral damage was also assessed using three specific serum markers: protein S-100-ß, neuron-specific enolase (NSE) and glial fibrillar acidic protein (GFAP) before the surgery, upon bypass completion, and in 16 hours after the operation.Results. The study revealed the incidence of delirium in 22.5%. When analyzing many factors of the intra- and postoperative period, it was found that the use of donor blood components in the primary volume of CPB filling was statistically significantly more often observed in patients with established delirium: 7 (78%) and 13 (42%) (p = 0.049). Also, it was found that levels of S-100-ß, NSE, and GFAP were significantly higher in patients with confirmed POD.The study described the incidence of POD in children after surgical treatment of congenital heart disease under cardiopulmonary bypass and showed that intraoperative transfusion was a risk factor for the development of delirium. The role of markers of cerebral damage in the diagnosis of POD was also proven.